2015
DOI: 10.1111/gcbb.12284
|View full text |Cite
|
Sign up to set email alerts
|

Exploring soil microbial 16S rRNA sequence data to increase carbon yield and nitrogen efficiency of a bioenergy crop

Abstract: Crop residues returned to the soil are important for the preservation of soil quality, health, and biodiversity, and they increase agriculture sustainability by recycling nutrients. Sugarcane is a bioenergy crop that produces huge amounts of straw (also known as trash) every year. In addition to straw, the ethanol industry also generates large volumes of vinasse, a liquid residue of ethanol production, which is recycled in sugarcane fields as fertilizer. However, both straw and vinasse have an impact on N 2 O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
76
1
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(103 citation statements)
references
References 78 publications
12
76
1
14
Order By: Relevance
“…(), Pitombo et al . () and Wang et al . (), among others, have used the emissions from non‐fertilized areas as background emissions to calculate the fertilizer EF.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…(), Pitombo et al . () and Wang et al . (), among others, have used the emissions from non‐fertilized areas as background emissions to calculate the fertilizer EF.…”
Section: Discussionmentioning
confidence: 91%
“…Specifically, in a sugarcane field, Pitombo et al . () observed that straw increases the abundance of Anaeromyxobacter sp., a taxon noted as an important reducer of N 2 O to N 2 . Under temperate conditions, Congreves et al .…”
Section: Discussionmentioning
confidence: 96%
“…Field measurements of the effects of crop residue harvest on GHG emissions are still limited in Brazil and over the world (Carmo et al, 2013;Baker et al, 2014;Jin et al, 2014;Signor et al, 2014;Pitombo et al, 2015). Most studies on this issue have used model simulations (Searchinger et al, 2008;Davis et al, 2012;Campbell et al, 2014;Liska et al, 2014;Zhao et al, 2015;Cardozo et al, 2016), as well as life cycle analysis assessments Bordonal et al, 2012Bordonal et al, , 2015.…”
Section: Impact Of Crop Residues On Ghg Emissionsmentioning
confidence: 99%
“…Major enzymes in soils include amylase, ␤-glucosidase, cellulase, chitinase, dehydrogenase, phosphatase, protease, and urease and are produced by various microbes (Dick and Tabatabai, 1984;Gupta et al, 1993;Makoi and Ndakidemi, 2008). Although new DNA sequencing technologies have made it possible to investigate microbial community composition (Torsvik and Øvreås, 2002;Cong et al, 2015;Hartmann et al, 2015;Pitombo et al, 2015), we have limited knowledge of the details of soil enzymes, such as their amounts, types, distribution, and efficiency, and little is known of individual microbial species and the corresponding enzyme(s) produced. The importance of soil enzymes to ecosystem functions, including soil respiration, has been reviewed by Makoi and Ndakidemi (2008).…”
Section: Soil Enzymes and Microbesmentioning
confidence: 99%